Financial inclusion: Globally important determinants - Peterson K. Ozili (Financial Internet Quarterly, 2021)
This paper highlights the globally-important determinants of financial inclusion. The determinants identified in this paper are formal account ownership; demand for formal savings; demand for formal borrowing; financial literacy and education; debit and credit card usage; the need to receive remittances from family and friends; size of the financial system; number of automated teller machines (ATMs); number of bank branches; proximity to a bank; availability and access to mobile phones; availability of digital financial products and services; technology infrastructure; government policy; culture and traditional belief systems; national financial inclusion strategy and implementation; and direct legislation.
Keywords: G00; G21; O16; 330; financial inclusion; determinants; unbanked adults; access to finance; digital finance; financial literacy